Efficacy of chemoprophylaxis for East African Zebu cattle exposed to trypanosomiasis in village herds in Kenya - Maloo, S.H.; Chema, S.; Connor, R.J.; Durkin, J.W.; Kimotho, P.G.; Maehl, H.M.; Mukendi, F.; Murray, M.; Rarieya, J.M.; Trail, J.C.M. (OAU/STRC, 1988)
Studies the efficacy of chemoprophylaxis for the control of trypanosomiasis on 700 heads of East African Zebu Cattle maintained in village herds in a tsetse-infested area at Muhaka, Coast province of Kenya. Shows the effect of trypanocidal drugs and time on trypanosome prevalence, and the effect of trypanocidal drugs and parasitaemia on blood packed cell volume (PCV) and on daily liveweight change